PSIGOSOSIALE BEHOEFTES VAN ADOLESSENTE DOGTERS MET SELF-MOORDGEDRAG - Du Toit, Andrea; Strydom, Herman (Social Work/Maatskaplike Werk, 2014)
This article focuses on the psychosocial needs of adolescent girls who present with suicidal behaviour, which can be attributed to a variety of circumstances. Qualitative interviewing was done with participants until data-saturation was achieved. The overarching psychosocial needs of participants were discussed in three main themes with specific sub-themes. The first theme focuses on love and acceptance; it has three sub-themes, namely a negative self-concept, parental rejection and peer group rejection. Theme two focuses on communication, with the expression of emotions, quality time and trust as sub-themes. The third theme discusses a certain future, with career choices and hope as sub-themes.